Interaction of Triethylamine with Phenylacetylene and Exciplex Formation Study in Solutions - Islam, Sahidul; Barman, Shrabani (Current Physical Chemistry, 2025)
IntroductionHydrogen bonding plays a very crucial role in weak molecular complex formation. Some of the binding modes may lead to fluorescence quenching or excited state complex formation. The fluorescent property of the gas phase complex of phenylacetylene-methylamine pair is different from that of the phenylacetylene-triethylamine pair.MethodsA total of 100 mM solution of triethylamine was added in 2 ml of 1 mM phenylacetylene taken in a cuvette. Then, absorption and fluorescence spectra were recorded, and fluorescence decay was measured each time. The experiment was conducted in the non-polar aprotic solvent, cyclohexane, and the polar protic solvent, ethanol.ResultsWith an increase in the concentration of triethylamine, fluorescence quenching occurred in the local emission band at 281nm in both cyclohexane and ethanol. Interestingly, in cyclohexane, an exciplex was formed that gave a structureless emission band at 422 nm, but not in ethanol.ConclusionIn cyclohexane, fluorescence quenching is predominantly dynamic in the lower range of concentrations of triethylamine, and beyond that, it is complicated due to exciplex formation. However, in ethanol, fluorescence quenching is purely dynamic in the entire range of concentrations of triethylamine.
Keywords: phenylacetylene